Structure–anticancer activity relationships among 4-azolidinone-3-carboxylic acids derivatives - Kaminskyy, D.V.; Lesyk, R.B. (Вiopolymers and Cell, 2010)
The aim of present research was investigation of anticancer activity of 4-azolidinone-3-carboxylic acids derivatives, and studies of structure–activity relationships (SAR) aspects. Methods. Organic synthesis; spectral methods; anticancer screening was performed according to the US NCI protocol (Developmental Therapeutic Program). Results. The data of new 4-thiazolidinone-3-alkanecarboxylic acids derivatives in vitro anticancer activity were described. The most active compounds which belong to 5-arylidene-2,4- thia(imida)zolidinone-3-alkanecarboxylic acids; 5-aryl(heteryl)idenerhodanine-3-succinic acids derivatives were selected. Determination of some SAR aspects which allowed to determine directions in lead-compounds structure optimization, as well as desirable molecular fragments for design of potential anticancer agents based on 4-azolidinone scaffold were performed. 5-Arylidenehydantoin-3-acetic acids amides were identified as a new class of significant selective antileukemic agents. Possible pharmacophore scaffold of 5-ylidenerhodanine-3-succinic acids derivatives was suggested. Conclusions. The series of active compounds with high anticancer activity and/or selectivity levels were selected. Some SAR aspects were determined and structure design directions were proposed.